A low-cost preparation method and product of alpha hemihydrate gypsum low-carbon products
By using α-hemihydrogypsum, silica sand or smelting slag and other materials for grinding, stirring and dry pressing under normal temperature and pressure conditions, the problem of existing high-energy-consuming products is solved, and efficient and low-cost low-carbon products are achieved.
Patent Information
- Application Number
- CN202310452046.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-25
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-04-25
AI Technical Summary
Existing sintered bricks and high-pressure steamed products require high energy consumption and high temperature and high pressure conditions during the production process, resulting in energy waste and high production costs.
Materials such as α-semi-water gypsum and silica sand or smelting slag are used to grind, stir and dry press mold according to specific ratios to avoid sintering and high-pressure steaming and sintering.
It realizes the rapid preparation of high-strength low-carbon products under normal temperature and pressure, reducing energy consumption and production costs, and high production efficiency.
Smart Images

Figure CN116496060B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and particularly relates to a low-cost preparation method of an alpha hemihydrate gypsum low-carbon product and the product. Background Art
[0002] CO2 emissions from the cement industry mainly come from the calcination and decomposition of limestone and the combustion of coal powder. According to statistics, cement production accounts for 8% of global carbon dioxide emissions, of which China's cement production accounts for 57% of the world's total, and China's cement production emissions account for 4.56% of global CO2 emissions. According to industry statistics, the production of 1 ton of cement emits about 940kg of CO2. In 2020, China's cement production was 2.377 billion tons, emitting 2.234 billion tons of carbon dioxide.
[0003] At present, most products on the market are sintered products and high-pressure steam-cured products, which are high-energy consumption products, such as sintered bricks, autoclaved aerated bricks, autoclaved standard bricks, etc., which are high-energy consumption products. Sintered bricks need to burn a lot of coal or solid waste to obtain energy, which will produce various polluting dust and waste energy; the production process of autoclaved products requires a lot of high-pressure steam, which also needs to burn a lot of coal or solid waste, which will produce various pollution and waste energy. Therefore, it is particularly important to develop a product that does not require sintering and high-pressure curing.
[0004] α-hemihydrate gypsum is a low-carbon and environmentally friendly building material produced by various processes using industrial by-product gypsum. It can not only absorb various industrial by-product gypsum, but also solve the current situation of large amounts of CO2 emitted during cement production. By mixing α-hemihydrate gypsum with various aggregates or industrial solid waste, high-strength products can be prepared and used in various construction industries.
[0005] The relevant patents have not been reported. The following are some patents for unfired bricks, with different methods.
[0006] The invention patent application for a kind of unburned brick and its preparation method (application number: 2021111941066, application publication date: 2022.02.08, publication number: CN114014618A) discloses that the present invention relates to a kind of unburned brick, and the weight proportions of its raw materials are as follows: 30-45 parts of waste asphalt concrete, 10-15 parts of recycled glass fiber, 15-20 parts of fly ash, and 15-20 parts of lime powder. The unburned brick is made of waste asphalt concrete and recycled glass fiber as main materials, fly ash and lime powder as auxiliary materials, 15-20 parts of water are added, stirred and mixed, and then made after pressing, molding and steaming. The preparation method comprises the following steps: crushing and sieving waste asphalt concrete; cutting and crushing waste glass fiber reinforced plastic plates to obtain glass fiber reinforced plastic recycled powder and glass fiber reinforced plastic recycled fiber; adding water to the treated waste asphalt concrete, treated recycled glass fiber reinforced plastic fiber, fly ash and lime powder according to a proportion, stirring the mixture evenly; weighing the mixture and pressing it into brick blanks; steaming and cooling the obtained brick blanks to obtain unfired bricks.
[0007] The technical problem with this patent application is that the technology requires a large amount of heat for steam pressing, which wastes energy, prolongs product production time, and increases production costs.
[0008] The invention patent application for a heat-insulating and environmentally friendly unfired brick and its preparation method (application number: 2021113492644, application publication date: 2022.01.28, publication number:) discloses a heat-insulating and environmentally friendly unfired brick and its preparation method, a plurality of bamboo-joint cylinders matching the unfired brick body are embedded in the middle of the unfired brick body, a plurality of the bamboo-joint cylinders are provided with a plurality of holes, and a plurality of the bamboo-joint cylinders are filled with polyurethane material, and the unfired brick body is prepared from yellow mud, slag powder, cement, aggregate, sodium hexafluoroaluminate polyester, coagulant, alkali activator, and wear-resistant agent; the preparation method of the heat-insulating and environmentally friendly unfired brick comprises the following steps: S1, preparing the unfired brick body; S2, preparing the polyurethane slurry; S3, assembling to obtain the heat-insulating and environmentally friendly unfired brick. The technical problem with this patent application is that the technology requires stirring at 60°C for 3 to 4 hours and curing at 70 to 80°C hot and humid conditions for 2 to 3 hours, which consumes a lot of energy, has a long production cycle and high production costs.
[0009] Invention patent application A kind of all-solid waste unburned brick prepared by using multi-industry solid waste and its preparation method (application publication date: 2022.01.14, application number: 2021114344071, publication number:) discloses a kind of all-solid waste unburned brick prepared by using multi-industry solid waste and its preparation method, and its preparation method is to mix 11-15wt% gelling material, 25-27wt% desulfurization ash, 60-62wt% stone powder and 12wt% water evenly, and then carry out static pressure molding and autoclave curing treatment to prepare a kind of unburned brick; wherein, the gelling material is composed of the following components: desulfurization ash 12-20wt%, calcium phosphate slag 1wt%, slag powder 60-71wt%, steel slag powder 16-19wt%. The technical problem of this patent application is that the technology needs high temperature and high pressure steam curing under the conditions of 160-190℃ and 0.8-1.5MPa, which wastes a lot of energy and increases the production cost of enterprises.
[0010] The main technical problems existing in the above background technology are:
[0011] At present, fired bricks and autoclaved products need to be under certain temperature or pressure to produce chemical reactions and produce bonding ability, and today's unfired bricks basically need heat curing or high-pressure curing, which is still a waste of energy. Concrete products can be cured at normal pressure, but it takes a long time, affecting production efficiency and construction efficiency.
[0012] The technical difficulty of solving the background technology lies in that it is difficult for various materials to quickly produce gelation under normal temperature and pressure conditions and reach the highest strength in a short time.
[0013] The significance of solving background technical problems and shortcomings: Solving the above problems can reduce the current high energy consumption and high resource consumption in the production process of sintered products and autoclaved products, reduce CO2 emissions in the process of calcining coal, and improve enterprise production efficiency and project construction efficiency, with significant social and economic benefits. Summary of the invention
[0014] The purpose of the present invention is to provide a low-cost preparation method for α-hemihydrate gypsum low-carbon products, so as to solve the problem that cement production currently emits too much carbon dioxide and various industrial solid wastes need to be treated urgently. The method is simple to prepare, does not require burning or steaming, and can quickly (within 2 days) reach the highest strength.
[0015] The technical solution of the present invention is:
[0016] The low-cost preparation method of α-hemihydrate gypsum low-carbon products of the present invention comprises the following steps: S1. grinding raw materials to a surface area of 220-600 m2 / kg to obtain ground micropowder, wherein the raw materials are silica sand or smelting slag; S2. weighing aggregate, ground micropowder and α-hemihydrate gypsum according to a proportion; S3. pouring the materials weighed in step S2 into a stirring device and stirring at a low speed for 1-2 minutes; S4. then adding water according to a water-to-material ratio of 0.06:1-0.1:1 and stirring for 2-3 minutes to obtain a uniform mixture; S5: transferring the mixture obtained in step S4 into a mold for dry pressing or extrusion molding; S6: demolding the product obtained in step S5 within 20-30 minutes to obtain the α-hemihydrate gypsum low-carbon product.
[0017] Optionally, in the above-mentioned low-cost preparation method of α-hemihydrate gypsum low-carbon products, the raw material of step S1 is silica sand.
[0018] Optionally, in the above-mentioned low-cost preparation method of α-hemihydrate gypsum low-carbon products, the smelting slag is refined steel slag, and the refined steel slag is ground to a fineness of 220 m2 / kg using a ball mill.
[0019] Optionally, in the above-mentioned low-cost preparation method of α-hemihydrate gypsum low-carbon products, the smelting slag in step S1 is ore-fired furnace slag, and the ore-fired furnace slag is ground to a fineness of 250 m2 / kg using a ball mill.
[0020] Optionally, in the above-mentioned low-cost preparation method of α-hemihydrate gypsum low-carbon products, in step S2, by weight, α-hemihydrate gypsum is 20-40 parts, the ground fine powder is 20-30 parts, and the aggregate is 29.94-60 parts.
[0021] Optionally, in the above-mentioned low-cost preparation method of α-hemihydrate gypsum low-carbon products, in step S3, the weighed materials are evenly mixed and poured into a stirring pot and stirred at a low speed for 90 seconds.
[0022] Optionally, in the above-mentioned low-cost preparation method of α-hemihydrate gypsum low-carbon products, in step S4, the water-to-material ratio is 0.08:1.
[0023] Optionally, in the above-mentioned low-cost preparation method of α-hemihydrate gypsum low-carbon products, in step S4, water is weighed and added into a stirring pot, mixed together with low-speed stirring for 60 seconds, and then high-speed stirring for 90 seconds, and the mixture is obtained after mixing evenly.
[0024] Optionally, in the above-mentioned low-cost preparation method of α-hemihydrate gypsum low-carbon products, step S6 is to demold the product obtained in step S5 within 25 minutes to obtain the product.
[0025] An alpha hemihydrate gypsum low-carbon product is prepared according to the low-cost preparation method of an alpha hemihydrate gypsum low-carbon product.
[0026] The beneficial effects of the present invention are:
[0027] Compared with sintered bricks on the market, the present invention solves the problems of high energy consumption and high pollution of sintered bricks, reduces excessive exploitation of raw materials, reduces production costs, and improves social and economic benefits.
[0028] Compared with the autoclaved standard bricks and autoclaved aerated bricks and their plates on the market, the present invention solves the problem of high energy consumption of autoclaved products, reduces production costs, and improves economic and social benefits.
[0029] Compared with the extrusion type plate production process, the present invention has the characteristics of fast production and high production efficiency, thus improving the economic benefits of the enterprise. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the specific implementation of the present invention or the technical solution in the prior art, the drawings required for use in the specific implementation or the description of the prior art are briefly introduced below.
[0031] Figure 1 It is a flow chart of the low-cost preparation method of α-hemihydrate gypsum low-carbon products of the present invention;
[0032] Figure 2 It is the experimental process and step flow chart of the present invention. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0034] A low-cost preparation method of α-hemihydrate gypsum low-carbon products comprises the following steps:
[0035] S1. Raw material grinding: Grind the raw material to a specific surface area of 220-㎡ / kg-600㎡ / kg to obtain finely ground powder, preferably 450㎡ / kg-600㎡ / kg, which is used as an active cementitious material. Specifically, according to the type of product to be prepared, the raw material is ground to a specific surface area of 220-㎡ / kg-600㎡ / kg using a ball mill. The raw material is silica sand or smelting slag, and the smelting slag is refined steel slag, slag or ore-heated furnace slag. The smelting slag contains a large amount of glass and has potential activity. After grinding, its activity can be fully stimulated. The larger the specific surface area, the higher the activity and the higher the strength of the product.
[0036] S2: weighing raw materials: using low-activity smelting solid waste such as refined steel slag or ore-heated furnace slag as aggregate, and weighing the aggregate, ground micro powder and α-hemihydrate gypsum according to the proportion, wherein, by weight, weigh 20-40 parts of α-hemihydrate gypsum, 20-30 parts of ground micro powder and 29.94-60 parts of aggregate;
[0037] Test the moisture content and particle size distribution of the aggregate and set aside. The moisture content of the aggregate is between 12% and 18%. The moisture content of the aggregate directly affects the water-to-material ratio in the later product preparation. According to different moisture contents, different water-to-material ratios are used to prepare products to obtain products with appropriate strength.
[0038] S3: Pour the weighed material in step S2 into a stirring device and stir at a low speed for 1-2 minutes; preferably, the weighed material can be evenly mixed and poured into a stirring pot and stirred at a low speed for 90 seconds.
[0039] S4. Add water and stir: Calculate the water-to-material ratio according to the moisture content of the aggregate, the water-to-material ratio is 0.06:1-0.1:1, add water and stir for 2-3 minutes to obtain a mixture. Preferably, weigh the water and add it to the mixing pot, stir at a low speed for 60 seconds, then stir at a high speed for 90 seconds, and stop;
[0040] S5: transferring the mixture obtained in step S4 into a mold for dry pressing or extrusion molding;
[0041] S6: demold the product obtained in step S5 within 20 to 30 minutes to obtain an α-hemihydrate gypsum low-carbon product. Preferably, demold the product obtained in step S5 within 20 minutes or 25 minutes.
[0042] The idea of the method of the present invention is to utilize the hydration characteristics, high adhesion and high early strength of α-hemihydrate gypsum, combined with the gelling properties of smelting slag powder, to bond the aggregates together well. The obtained low-carbon product has an absolute dry compressive strength of more than 25MPa and a dry bulk density of 478-525kg / m 3 .
[0043] Experimental procedures
[0044] The present invention selects raw materials and weights according to the following procedures:
[0045] Raw material grinding: After drying the smelting slag or slag, use a ball mill to grind it to a specific surface area of 220㎡ / kg~600㎡ / kg, preferably 450㎡ / kg~600㎡ / kg, and use it as an active cementitious material; low-activity solid waste or low-activity tailings can also be dried and ground to use as an active cementitious material.
[0046] Raw material weighing: Use low-activity smelting solid waste such as refined steel slag or ore-heated furnace slag as aggregate. The moisture content of refined steel slag or ore-heated furnace slag is between 12% and 18%. Weigh the low-activity solid waste aggregate, ground micropowder and α-gypsum according to the proportion, including 20-40 parts of α-hemihydrate gypsum, 20-30 parts of ground micropowder and 29.94-60 parts of aggregate, and the water-to-material ratio is 0.06:1 to 0.1:1.
[0047] Slow stirring and mixing: Place the materials weighed in the previous step into the stirring device and stir at low speed for 90 seconds.
[0048] Add water and mix together: Calculate the water-to-aggregate ratio according to the moisture content of aggregate, the water-to-aggregate ratio is 0.06:1~0.1:1, weigh the water and add it into the mixing pot, mix together at low speed for 60 seconds, then at high speed for 90 seconds, and stop.
[0049] Moulding: Pour the mixed material into the mould.
[0050] Pressure forming: Place it under the press and apply 25-30 MPa pressure.
[0051] Standing: Let the pressed product stand at room temperature for 20 to 30 minutes.
[0052] Demoulding: Demould the product after the standing time is up.
[0053] Measure 2h strength: Measure the 2h compressive strength from the start of stirring to 2h.
[0054] Measure 4h strength: Measure the 4h compressive strength from the start of stirring to 4h.
[0055] Measure the strength after constant weight: Put the demoulded product into a drying oven, dry it at 105℃ until it reaches constant weight, and measure the compressive strength after constant weight.
[0056] Embodiment 1:
[0057] A low-cost preparation method of α-hemihydrate gypsum low-carbon products comprises the following steps:
[0058] S1: Test the moisture content and particle size distribution of silica sand, and prepare refined steel slag with a moisture content of 15%.
[0059] S2: Use an electronic weighing scale to mix the following ingredients by weight: 20 parts of α-hemihydrate gypsum, 20 parts of ground micro powder, and 60 parts of aggregate silica sand, with a water-to-material ratio of 0.06:1;
[0060] S3: The raw materials obtained in step S1 are uniformly mixed according to the proportions of step S2, poured into a stirring pot, and stirred at a low speed for 2 minutes. After the mixture is uniform, water is added and stirred for 3 minutes to obtain a uniform mixture;
[0061] S4: transferring the mixture obtained in step S3 into a mold for dry pressing;
[0062] S5: The product obtained in step S4 is demoulded within 25 minutes to obtain the product.
[0063] The low-carbon product has an absolute dry compressive strength of 20 MPa and a dry bulk density of 525 kg / m3.
[0064] Embodiment 2:
[0065] A low-cost preparation method of α-hemihydrate gypsum low-carbon products comprises the following steps:
[0066] S1: Grind the refined steel slag to a fineness of 220㎡ / kg using a ball mill according to the type of product to be prepared;
[0067] S2: Test the moisture content and particle size distribution of refined steel slag, and prepare the slag with a moisture content of 17%.
[0068] S3: Use an electronic weighing scale to mix the following ingredients by weight: 35 parts of α-hemihydrate gypsum, 20 parts of ground micro powder and 45 parts of aggregate refined steel, with a water-to-material ratio of 0.1:1;
[0069] S4: the raw materials obtained in step S2 are uniformly mixed according to the proportions of step S3, poured into a stirring pot, stirred at a low speed for 1 minute, and after the mixture is uniform, water is added and stirred for 2 minutes to obtain a uniform mixture;
[0070] S5: transferring the mixture obtained in step S4 into a mold for dry pressing or extrusion molding;
[0071] S6: The product obtained in step S5 is demoulded within 20 minutes to obtain the product.
[0072] The low-carbon product has an absolute dry compressive strength of 25 MPa and a dry bulk density of 490 kg / m3.
[0073] Embodiment 3:
[0074] A low-cost preparation method of α-hemihydrate gypsum low-carbon products comprises the following steps:
[0075] S1: Grind the ore-fired slag to a fineness of 250 m2 / kg using a ball mill according to the type of product to be prepared;
[0076] S2: Test the moisture content and particle size distribution of the slag of the ore-fired furnace and set it aside for use; nickel-iron slag with a moisture content of 8%.
[0077] S2: Use an electronic weighing scale to mix the following ingredients by weight: 40 parts of α-hemihydrate gypsum, 20 parts of ground micro powder and 40 parts of aggregate ore-fired slag, with a water-to-material ratio of 0.08:1;
[0078] S3: The raw materials obtained in step S1 are uniformly mixed according to the proportions of step S2, poured into a stirring pot, and stirred at a low speed for 1.5 minutes. After the mixture is uniform, water is added and stirred for 2.5 minutes to obtain a uniform mixture;
[0079] S4: transferring the mixture obtained in step S3 into a mold for dry pressing or extrusion molding;
[0080] S5: The product obtained in step S5 is demoulded within 25 minutes to obtain the product.
[0081] The low-carbon product has an absolute dry compressive strength of 29 MPa and a dry bulk density of 480 kg / m3.
[0082] Example 4
[0083] A low-cost preparation method of α-hemihydrate gypsum low-carbon products comprises the following steps:
[0084] S1: Grind the ore-fired slag to a fineness of 250 m2 / kg using a ball mill according to the type of product to be prepared;
[0085] S2: Test the moisture content and particle size distribution of the slag, and set aside; Steel slag with a moisture content of 5%
[0086] S2: Use an electronic weighing scale to mix the following ingredients by weight percentage: 20.02 parts of α-hemihydrate gypsum, 30 parts of ground micro powder, 49.9 parts of aggregate, with a water-to-material ratio of 0.08:1;
[0087] S3: The raw materials obtained in step S1 are uniformly mixed according to the proportions of step S2, poured into a stirring pot, and stirred at a low speed for 1-2 minutes. After the mixture is uniform, water is added and stirred for 2-3 minutes to obtain a uniform mixture;
[0088] S4: transferring the mixture obtained in step S3 into a mold for dry pressing or extrusion molding;
[0089] S5: The product obtained in step S4 is demoulded within 25 minutes to obtain the product.
[0090] The low-carbon product has an absolute dry compressive strength of 22MPa and a dry bulk density of 510kg / m 3 .
[0091] The low-cost preparation method of α-hemihydrate gypsum low-carbon products of the present invention is simple to prepare, free of burning and steaming, and can quickly (within 2 days) reach the highest strength, avoiding high energy consumption and high pollution, reducing the excessive exploitation of raw materials, and reducing production costs. It has the characteristics of fast production and high production efficiency, and improves economic and social benefits.
[0092] The above specific implementation is a preferred embodiment of the present invention and cannot limit the present invention. Any other changes or other equivalent replacement methods that do not deviate from the technical solution of the present invention are included in the protection scope of the present invention. The above is only a preferred embodiment of the present invention and is only illustrative, not restrictive, for the present invention. Those skilled in the art understand that many changes, modifications, and even equivalences can be made to it within the spirit and scope defined by the claims of the present invention, but they will all fall within the protection scope of the present invention.
Claims
1. A low-cost preparation method for α-hemihydrate gypsum low-carbon products, characterized in that: The following steps are included: S1. Grinding the raw material to a specific surface area of 220 m2 / kg~600 m2 / kg to obtain a finely ground powder, wherein the raw material is silica sand or mineral thermal slag; S2. The aggregate, ground powder and α hemihydrate gypsum are weighed according to the ratio, by weight, α hemihydrate gypsum is 20-40 parts, ground powder is 20-30 parts, and aggregate is 29.94-60 parts, wherein the aggregate is silica sand or ore-fired slag; S3. Pour the weighed material in step S2 into the mixing device and stir at low speed for 1-2 minutes; S4. Then add water and stir for 2-3 minutes according to the water-to-material ratio of (0.06~0.1):1 to obtain a uniform mixture; S5: transferring the mixed material obtained in step S4 into a mold for extrusion molding; S6: demold the product obtained in step S5 within 20 to 30 minutes to obtain the α-hemihydrate gypsum low-carbon product.
2. The low-cost preparation method of α-hemihydrate gypsum low-carbon products according to claim 1, characterized in that: The raw material of step S1 is silica sand.
3. The low-cost preparation method of α-hemihydrate gypsum low-carbon products according to claim 1, characterized in that: The ore-fired slag is ground into powder with a ball mill to a fineness of 250 m2 / kg.
4. The low-cost preparation method of α-hemihydrate gypsum low-carbon products according to claim 1, characterized in that: In step S3, the weighed materials are uniformly mixed and poured into a stirring pot and stirred at a low speed for 90 seconds.
5. The low-cost preparation method of α-hemihydrate gypsum low-carbon products according to claim 1, characterized in that: In step S4, the water-to-material ratio is 0.08:
1.
6. The low-cost preparation method of α-hemihydrate gypsum low-carbon products according to claim 1, characterized in that: In step S4, water is weighed and added into a stirring pot, mixed together with low-speed stirring for 60 seconds, and then high-speed stirring for 90 seconds, and the mixture is obtained after mixing evenly.
7. The low-cost preparation method of α-hemihydrate gypsum low-carbon products according to claim 1, characterized in that: The step S6 is to demould the product obtained in step S5 within 25 minutes to obtain the product.
8. An α-hemihydrate gypsum low-carbon product, characterized in that: The α-hemihydrate gypsum low-carbon product is prepared according to the low-cost preparation method of the α-hemihydrate gypsum low-carbon product according to any one of claims 1-7.
Citation Information
Patent Citations
Baking-free brick and preparation method thereof
CN114014618A
Baking-free brick taking iron tailings as raw material and preparation method of baking-free brick
CN115925344A